2019
DOI: 10.1155/2019/7932193
|View full text |Cite
|
Sign up to set email alerts
|

Contamination Potentials of Household Water Handling and Storage Practices in Kirundo Subcounty, Kisoro District, Uganda

Abstract: Introduction. Waterborne diseases constitute a major public health burden in developing and underdeveloped countries. Consumption of contaminated water causes health risk to the public, and the situation is alarming in rural areas. The objective of this study was to assess the contamination potentials of different house water handling and storage practices in the Kirundo subcounty, Kisoro District, Uganda. Material and Methods. A cross-sectional and descriptive study in which 344 water samples were collected r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 10 publications
6
35
0
Order By: Relevance
“…Several epidemiological studies in Uganda have attributed cholera outbreaks to use of contaminated surface water [20,21,24,63]. Furthermore, studies conducted on the surface water focus on pathogen identification [63,64] leaving out the water physicochemical parameters which are equally important in the provision of safe drinking water [53] and are necessary for survival of all living organisms (both animals and plants) [44].…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies in Uganda have attributed cholera outbreaks to use of contaminated surface water [20,21,24,63]. Furthermore, studies conducted on the surface water focus on pathogen identification [63,64] leaving out the water physicochemical parameters which are equally important in the provision of safe drinking water [53] and are necessary for survival of all living organisms (both animals and plants) [44].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of these bacteria suggests a recent fecal contamination and an epidemiological hazard from a potential finding of pathogenic microorganisms. Most drinking water sources were found to have coliform counts above the recommended national and international guidelines [2]. Research in Jakarta shows that bouts of diarrhea, reported in one-third of households were closely related to water contaminated with more than 100 fecal coliform bacteria in 100 mL of water samples [40].…”
Section: Microbiological Water Quality Monitoringmentioning
confidence: 99%
“…The risks associated with consumption of contaminated water is because of failure in securing optimal hygiene management practices at both formal and informal settings. Water quality encompasses physical, chemical and biological properties that are supposed to be in line with the required specifications (Agensi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Their presence is suggestive of other infective pathogens of fecal origin such as E. coli (Bandekar et al, 2006;Nwachukwu and Otokunefor, 2006). Besides traditional methods of detecting coliform bacteria, water quality factors have also been used as significant predictors of fecal coliform bacteria (Seo et al, 2019;Hayashi, 2004). In many middle and low-income countries, cases of microbial contamination of water are linked to unwholesome practices, lack of water treatment at the point of use and unhygienic management of water sources (Agensi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%